Biorreguladores vegetais, substratos e estaquia em Lippia origanoides Kunth (verbenaceae) - Silva, Gabriela Carinhanha (2012)
This study aimed to evaluate the influence of substrate and application of exogenous auxin on cuttings and the effect of plant bioregulators on growth, production and chemical composition of essential oil of Lippia origanoides Kunth. Cuttings were treated with indolebutyric acid (IBA) at concentrations of 0, 62,5, 125, 250 and 500 mg L-1 and cultivated on expanded vermiculite, Biomix® and expanded vermiculite + Biomix® (1:1). We evaluated the percentage of rooting and survival, stem and the largest root length, leaf number, leaves, stem, root and total dry mass. Moreover, aldult plants were sprayed with gibberellic acid, 6-benzylaminopurine, acetylsalicylic acid, jasmonic acid, Stimulate®, we evaluated at three different times height, roots length, leaf area, leaves, twigs, roots, inflorescences and total dry matter, and yield, content and composition of essential oil. We calculated relative growth rate, net assimilation rate, leaf weight ratio and specific leaf area. It was found that Lippia origanoides has easy rooting and the use of 278 mg L¹ of IBA and cultivation on Biomix® + vermiculite (1:1) is more efficient for its propagation. Bioregulators stimulate growth of L. origanoides in the experimental conditions for extended periods. The application of bioregulators, mainly jasmonic acid and Stimulate® elevates the content of essential oil, whose major components are carvacrol, γ-terpinene, ρ-cymene, (E)-caryophyllene, bicyclogermacrene and thymol. The concentration of these compounds in plants L. origanoides varies with time and bioregulators, except bicyclogermacrene.